The Ｒectifiercircuit Fault Diagnosis Based on the BP Neural Network - JIANG Yan-shu; WU Di; WANG Wei-liang (Journal of Harbin University of Science and Technology)
Due to the new power electronic products improving and many qualities are growing，making the online fault diagnosis of power electronic circuit becomes more important. In this paper，simulation model is established by using MATLAB to obtain output voltage. Then we use the Fourier analysis method to extract the DC component，the amplitude，the second harmonic and harmonic amplitude three times. After these values are normalized，we set them into the BP network to receive six numbers in order to determine fault location and fault point. Taking three phase bridge rectifier circuit as an example with this method，the test error value is less than 10 －4. The experiment result shows that this method has merit of higher diagnostic rate，higher reliability and widely application.